Application of single-incision transvaginal mesh in a woman undergoing peritoneal dialysis and suffering from refractory advanced stage pelvic organ prolapse - Yi-Hung Sun; Wei-Chih Kan; Ming-Ping Wu (Wolters Kluwer Medknow Publications, 2017)
Objective: We would like to provide an option of minimal invasive surgical intervention for a patient with end-stage renal disease undergoing continuous ambulatory peritoneal dialysis, who was at the advanced-stage pelvic organ prolapse (POP) and who also failed to be treated conservatively. Materials and method: We present a case of uterine prolapse stage IV in a woman who underwent continuous ambulatory peritoneal dialysis due to end-stage renal disease. Her severity of POP had only limited improvement after being switched to hemodialysis and vaginal cream use. After her informed consent, we performed a uterus-sparing transvaginal mesh procedure to adjust the anterior, apical, and posterior defects of pelvis. Results: There has been no recurrence of any compartment of POP during the 16-month follow-up period, nor any mesh-related complications. The perineal swelling subsided after switching to nocturnal automated peritoneal dialysis only in the supine position. Conclusion: Patients with POP at an advanced stage during peritoneal dialysis who failed to be treated conservatively may require a surgical intervention. Uterus-sparing transvaginal mesh was a feasible minimal invasive option.